ANALISIS KINERJA PEGAWAI DI BADAN LINGKUNGAN HIDUP KOTA SEMARANG - TG, Sternahirunda,; Nurcahyanto, Herbasuki (Journal of Public Policy and Management Review, 2016)
This research is purposed to analyze and describe the performance of employees at the Environment Agency of Semarang City using employee performance assessment indicators, and the factors that affect employee performance. This research uses qualitative descriptive study with data collection through interviews, observation, documentation, and literature study. Informants were taken by researchers is the head of the field, the head of sub-fields, and employees at the Environment Agency of Semarang City. In this research, the researcher uses an indicator of employee performance from John Miner. Indicator of quality is not good enough, employees do not understand about their duties and functions, and they still make mistakes while working. The indicator of quantity is not good enough constrained by the lack of Human Resource and other obligations outside the office. The use of working time is not good enough, the employee can not use their time effectively. Researcher also analyzed the factors that affect the performance of employees from Dale Timple. The employee competence is not good enough, knowledge and skills of employees work still lacking. The employee discipline is not good enough, employees still often violate the rules office. The work environment is not good enough, it is less room lighting, the air temperature is hot altough there are air conditioners, the noise due to the building process and traders coming into the room, and the office layout is cramped and not really tidy. Based on the research,we can conclude that the performance of employees at the Environment Agency of Semarang City is not good enough. Recommendations that given by the researcher is employees need education and training to improve their quality of human resources, need to increase the amount of human resources, applying finger printing for absent employees, providing strict sanctions for employees who are not discipline, and complementary facilities and infrastructure that support employee performance.